1953
DOI: 10.1172/jci102774
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Prevention of Rheumatic Fever: The Effect of Time of Initiation of Treatment of Streptococcal Infections on the Immune Response of the Host 1

Abstract: Previous studies have established the fact that penicillin treatment of acute streptococcal pharyngitis results in a marked suppression of antibody formation (1,2,3). This is in contrast to the failure of penicillin treatment to alter the immune response in patients with pneumococcal pneumonia (4). It has been suggested that in the latter case, sufficient pneumococcal antigen is formed during the early phases of pneumonia to provide a maximal antigenic challenge before penicillin therapy is instituted (4). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

1956
1956
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…This failure of penicillin to prevent completely the formation of antistreptolysin, in spite of the apparent eradication of the streptococcus and the complete inhibition of type-specific antibody, suggests that the major antigenic stimulus to the formation of antistreptolysin occurs early in the course of streptococcal infections, while the stimulus to the formation of type-specific antibody occurs over a much longer period. This observation is in agreement with data reported by Brock and Siegel (15). These authors found that treatment of streptococcal pharyngitis with penicillin within 31 hours after the onset of the disease was more effective in the suppression of antistreptolysin formation than therapy delayed for 3 or 5 days.…”
Section: Eaureomycin (22 Patients)supporting
confidence: 92%
“…This failure of penicillin to prevent completely the formation of antistreptolysin, in spite of the apparent eradication of the streptococcus and the complete inhibition of type-specific antibody, suggests that the major antigenic stimulus to the formation of antistreptolysin occurs early in the course of streptococcal infections, while the stimulus to the formation of type-specific antibody occurs over a much longer period. This observation is in agreement with data reported by Brock and Siegel (15). These authors found that treatment of streptococcal pharyngitis with penicillin within 31 hours after the onset of the disease was more effective in the suppression of antistreptolysin formation than therapy delayed for 3 or 5 days.…”
Section: Eaureomycin (22 Patients)supporting
confidence: 92%
“…In this study, clindamycin and K penicillin V equally suppressed ASO responses. Also, in this and in several previous studies (2,4,21), antistreptococcal therapy incompletely prevented a significant ASO response despite complete eradication of group A streptococci and early institution of therapy. There is no relation between the development of ASO and type-specific streptococcal antibody.…”
supporting
confidence: 62%
“…The studies were all hospital-based, 8 out of 10 of which were conducted at U.S. military hospitals from 1950 to 1957 [16,18-24]. Only 3 of the studies used placebos for the control group [20,21,23]. The remainder used either no treatment or symptomatic treatment as controls.…”
Section: Resultsmentioning
confidence: 99%
“…Nine out of the ten studies reviewed date back to the 1950's when randomised trial methods were still evolving and good guidelines for conducting trials were not yet available [16-24]. Regarding randomisation and allocation concealment, two trials used shuffled cards and were considered to be truly randomised [20,21]. The remaining studies were categorized as 'quasi-randomised' as allocation was based on methods such as Air Force Serial number, and date of hospital admission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation